1975
DOI: 10.1111/j.1432-1033.1975.tb21038.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Synthesis of a Lipid‐Containing Bacteriophage

Abstract: Enzymes of glycerophosphatide biosynthesis and degradation have been characterized using membrane fractions of Pseudomonas BAL-31, the host cell of the lipid-containing bacteriophage PM2. Inner and outer membrane fractions were investigated. Whereas the outer membrane contained more phosphatidylethanolamine and less phosphatidylglycerol than the inner membrane, the fatty acid composition was almost the same for both membranes. The pathway for glycerophosphatide biosynthesis was the same as that for Escherichia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…1. Enzymes capable of synthesizing some of these same phospholipids have been reported in Bacillus PP (15), Bacillus licheniformis (12), Salmonella typhimurium (1), Pseudomonas BAL 31 (21), and Micrococcus cerificans (14). Eucaryotic cells have similar pathways (22) leading to all of these phospholipids except for phosphatidylserine and phosphatidylethanolamine.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…1. Enzymes capable of synthesizing some of these same phospholipids have been reported in Bacillus PP (15), Bacillus licheniformis (12), Salmonella typhimurium (1), Pseudomonas BAL 31 (21), and Micrococcus cerificans (14). Eucaryotic cells have similar pathways (22) leading to all of these phospholipids except for phosphatidylserine and phosphatidylethanolamine.…”
mentioning
confidence: 93%
“…However, the phosphatidylserine synthase from E. coli was unexpectedly found tightly associated with the ribosomal fraction of cells broken by several techniques (18). This latter enzymatic activity has been reported to be membrane associated in both Pseudomonas BAL 31 (21) and Bacillus PP (15). Therefore, the phosphatidylserine synthase of E. coli is the only reported enzyme involved in phospholipid biosynthesis that is not found tightly associated with a membrane structure.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The study of this group of enzymes is important because their action is involved in structural as well as functional properties of cell membranes. The phospholipid biosynthetic enzymes have been extensively studied in several gram-negative bacteria (3,19,23,28). These enzymes have been investigated in only three species of gram-positive bacilli (14,16,21), and only acyltransferase activities have been reported for the gram-positive anaerobe Clostridium butyricum (11).…”
mentioning
confidence: 99%
“…phosphatidylethanolamine + C02 Reactions 2 and 4 have also been shown to utilize dCDP-diglyceride. These reactions have also been found in other facultative and aerobic bacteria (5,19,21,26). Because no comparable work had been done with anaerobic bacteria, we carried out a study of phospholipid-synthesizing enzymes in Clostridium butyricum and found that reactions 1 through 4 were present (25); however, phosphatidylserine decarboxylase activity was barely detectable (25).…”
mentioning
confidence: 83%